Isolation of Biosurfactant-Producing Bacteria from Petroleum- Polluted Mangrove Swamp Samples Using Selective Enrichment Procedure: NA - Uzoigwe, C. I.; Scrivens, J.; Bello, A. (European Journal of Applied Sciences, 2022)
Fifty-five morphologically distinct isolates were obtained from crude oil polluted mangrove swamp samples collected from Niger-Delta, region of Nigeria, using three microbiological media for selective enrichment. Isolation from the cultivation media was performed at 3 intervals (Days 3, 7 and 14). 35% of filamentous/irregular shaped colonies were obtained at longer incubation (Day 14) and 80% of colonies were gram positive rods. Cell-free supernatants from twenty-two isolates indicated biosurfactant activity in one or all test media (Nutrient medium (NB), NB + 2% glycerol and Mineral salt medium + 2% glucose) based on results from five screening tests; surface tension, emulsification index, oil displacement, drop collapse and haemolysis. These isolates demonstrated medium-dependent biosurfactant synthesis with 16 isolates producing biosurfactant in NB + 2% glycerol compared to other test media. Results of surface tension reduction ranged from 29.8 to 48.6 mN m-1 but results did not correlate well with emulsification index, hence combination of screening methods was essential for confirmation of biosurfactant-producing isolates. 16SrRNA sequencing identified isolates belonging to Bacillus, Serratia and Paenibacillus genera. Among these isolates, SB14-1 identified as Bacillus humi utilised three test media showing ST reduction (34.1 to 48.6 mN m-1) and emulsification of paraffin oil (49.1 to 62.6%). To date, there are no reports of biosurfactant synthesis from Bacillus humi amongst other Bacillus species. The use of selective enrichment media and combination of biosurfactant screening tests could be a successful approach towards isolation of possibly new biosurfactant-producing strains and/or hyper-producers.